Study of J-V Characteristics of Microcrystalline Silicon Solar Cell on The Structure of P-I-N Homojunction - Dewi, Yuningtyas Nely Kusuma; Purwandari, Endhah; Anwar, Khoirul; Misto, Misto (Computational And Experimental Research In Materials And Renewable Energy, 2020)
Microcrystalline silicon (μc-Si) is a silicon semiconductor material with a crystalline structure in the amorphous phase. Here, the transport phenomenon in this phase has been modeled to produce charge carrier distribution profile and current density-voltage characteristics. The calculations were obtained by solving Poisson and Continuity equations on crystal and amorphous materials which are modeled in one-dimensional p-i-n homojunction, using finite element method. The simulation results of the charge carrier distribution profile show that the highest electron concentration in the n-layer of 1018 cm-1, and the highest hole concentration in the p-layer of 1018 cm-1. The result current density-voltage (J-V) characteristics curve show that the open circuitt voltage of 0,6 volts and short-circuit current density of 26.4 mA/cm. The energy conversion efficiency of 9.02% with a fill factor of 0.569.